Field Manual of Michigan Flora - Voss, Edward G. (Edward Groesbeck), 1929- (Book collections on Project MUSE., 2012)
Field Manual of Michigan Flora is the most up-to-date guide available for all seed plants growing wild in Michigan. Significantly expanding and updating the three-volume Michigan Flora, the book incorporates the discoveries of numerous additional species, recent systematic research, and a vast trove of new information on the shifting distributions of Michigan species. It presents concise identification keys, information about habitats, and completely updated distribution maps for all the seed plants, native or naturalized, that have been recorded from the state, fully treating over 2,700 species. All non-native species are included with notes on their first discovery in the state and comments on invasive tendencies. Rare native species that appear to be declining or to have shrinking ranges are also noted. This book is an essential reference for anyone interested in appreciating Michigan's natural heritage and understanding our ever-changing environment.